PERSEPSI DAN PENGALAMAN IBU TENTANG PRAKTIK PEMBERIAN ASI EKSKLUSIF DI MEDAN : STUDI FENOMENOLOGI - GIRSANG, ELIZABETH SEPTIANUR (LP2MTBM MAKARIOZ, 2023)
Medan City is one of the cities in North Sumatra province which has a number of mothers who gave birth in hospital as many as 125 people, where the problem that arises in the increase and perception regarding exclusive breastfeeding is the low understanding of mothers in carrying out the breastfeeding process, such as low understanding of baby breastfeeding techniques, available resources for counseling in carrying out the breastfeeding process in hospitals, lack of understanding of the benefits of breastfeeding, and lack of understanding of the substances contained in breast milk. This research aims to understand and analyze the extent to which the perceptions and experiences of mothers who have given birth in Medan City can increase their knowledge about the practice of breastfeeding their babies. The method used in this research is the analytical descriptive method. The population in this study was 125 mothers who were giving birth in hospitals in Medan City, and the sample taken in this study was 78 mothers who were giving birth in hospitals in Medan City. The data collection technique is carried out using documentation studies. The results of the research explain that mothers who experience the process of giving birth to babies in hospitals in Medan City who have good perceptions and experience in providing exclusive breastfeeding are mothers in the age range of 30-34 years, while mothers who are experiencing the process of giving birth to a child which many answered and thought that the practice of giving birth to breast milk was less than optimal due to the lack of mothers having experience in giving breast milk in baby feeding techniques amounting to 28 respondents, as well as mothers who were experiencing the process of giving birth to a child who answered a lot and thought that the practice of giving breast milk was lacking. maximum, so that there is a perception that there is a lack of resources available for counseling in carrying out the breastfeeding process in hospitals by 27 respondents.